2022
DOI: 10.2166/wst.2022.283
|View full text |Cite
|
Sign up to set email alerts
|

Fenton process for the treatment of wastewater effluent from the edible oil industry

Abstract: The present study intends to investigate the performance of the Fenton reaction as one of the most efficient (AOPs) in a batch mode for treating wastewater effluent from the edible oil industry, as well as the parameters that influence the reaction, such as pH, hydrogen peroxide (H2O2), and ferrous sulfate heptahydrate (FeSO4.7H2O) doses at various reaction times. The response surface methodology (RSM) was applied with a central composite design (CCD) for optimizing the responses of pollutant removals. The obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Statistical analysis concluded that FeSO 4 is more important than H 2 O 2 in removing certain organic materials; however, H 2 O 2 plays a more significant role than FeSO 4 in removing effluents. [27] In a study by Ayoub et al (2022), the performance of the Fenton reaction was suggested as one of the most efficient advanced oxidation processes (AOPs) in batch mode for treating wastewater from the edible oil industry. The research- ers investigated parameters affecting the reaction, applying central composite design (CCD) and response surface methodology (RSM) to optimize contaminant removal responses.…”
Section: Tbars Levelsmentioning
confidence: 99%
“…Statistical analysis concluded that FeSO 4 is more important than H 2 O 2 in removing certain organic materials; however, H 2 O 2 plays a more significant role than FeSO 4 in removing effluents. [27] In a study by Ayoub et al (2022), the performance of the Fenton reaction was suggested as one of the most efficient advanced oxidation processes (AOPs) in batch mode for treating wastewater from the edible oil industry. The research- ers investigated parameters affecting the reaction, applying central composite design (CCD) and response surface methodology (RSM) to optimize contaminant removal responses.…”
Section: Tbars Levelsmentioning
confidence: 99%
“…One area where the Fenton reaction is used beneficially is the treatment of wastewater. Fenton reaction is often used to treat "oily wastewater" which is water that contains fats and greases (Ayoub, 2022). Hydroxyl radicals are able to degrade the organic pollutants and effectively remove the oils and other harmful molecules from the wastewater.…”
Section: Fenton Reaction Implications/applicationsmentioning
confidence: 99%
“…[8][9][10] But the high cost of Pt and metals of this group makes to look for more affordable materials to meet the needs of the industry. Famous Fenton process, which is the decomposition of hydrogen peroxide under the action of iron salts, which can be described by Equation ( 1): [7,[11][12][13][14][15][16]…”
Section: Introductionmentioning
confidence: 99%
“…But the high cost of Pt and metals of this group makes to look for more affordable materials to meet the needs of the industry. Famous Fenton process, which is the decomposition of hydrogen peroxide under the action of iron salts, which can be described by Equation : [7,11–16] Fe2++H2O2Fe3++OH+OH-. $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm Fe}{^{2+}}+{\rm H}{_{2}}{\rm O}{_{2}}\rightarrow {\rm Fe}{^{3+}}+{\rm OH}{^{\bullet}}+{\rm OH}{^{- . }}\hfill\cr}}$ …”
Section: Introductionmentioning
confidence: 99%